Phage display for the detection, analysis, disinfection, and prevention of Staphylococcus aureus. Issue 1 (23rd December 2022) - Tian, Lei; Jackson, Kyle; Chan, Michael; Saif, Ahmed; He, Leon; Didar, Tohid F.; Hosseinidoust, Zeinab
Abstract: The World Health Organization has designated Staphylococcus aureus as a global health concern. This designation stems from the emergence of multiple drug‐resistant strains that already account for hundreds of thousands of deaths globally. The development of novel treatment strategies to eradicate S. aureus or mitigate its pathogenic potential is desperately needed. In the effort to develop emerging strategies to combat S. aureus, phage display is uniquely positioned to assist in this endeavor. Leveraging bacteriophages, phage display enables researchers to better understand interactions between proteins and their antagonists. In doing so, researchers have the capacity to design novel inhibitors, biosensors, disinfectants, and immune modulators that can target specific S. aureus strains. In this review, we highlight how phage display can be leveraged to design novel solutions to combat S. aureus . We further discuss existing uses of phage display as a detection, intervention, and prevention platform against S. aureus and provide outlooks on how this technology can be optimized for future applications. Abstract : Phage display is broadly used for detection, mapping, disinfection, and prevention of Staphylococcus aureus.